Analysis Of Sme Financing And Shock Variables At Indonesia's Sharia Rural Banks (Bprs) In Indonesia - Yaman, Afdhal; Nihaya, Ina Uswatun; Shalihah, Mar'atun; Tuanany, Ismail; Manilet, Aisa; Hulihulis, Nur Sasma Sabila (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
This study investigates the effects of macroeconomic shock variables, namely inflation, the BI rate, and the exchange rate, on SME financing in Indonesia’s Sharia Rural Banks (BPRS). This research employs a quantitative approach using time-series data from April 2016 to August 2023, comprising 89 observations, and is analyzed using EViews 10. The results show that inflation has a more stable and dominant effect on SME financing cycles, whereas the BI rate and exchange rate exhibit heterogeneous and time-varying influences. Moreover, the contribution of inflation to SME financing in BPRS tends to increase over time. This study contributes to the Islamic finance literature by demonstrating a distinctive transmission mechanism of macroeconomic shocks within Sharia-based rural banking, which operates under profit-and-loss sharing and asset-backed financing principles. From a policy perspective, the findings suggest that maintaining price stability is crucial for sustaining SME financing growth in the Islamic banking sector. Therefore, Bank Indonesia (BI) should prioritize inflation control, while the Financial Services Authority (OJK) needs to strengthen prudential supervision to enhance BPRS resilience against external volatility. In addition, BPRS management is encouraged to improve risk management and portfolio strategies to mitigate macroeconomic uncertainty and ensure financing sustainability.